1993
DOI: 10.1115/1.2910643
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection in the Inclined, Cranked Thermosyphon

Abstract: Consideration is given to natural convection in a cranked, tubular thermosyphon oriented in various ways with respect to the vertical. Experiments on a small-bore, water-filled tube are used to investigate three orientational effects: by tilting in a vertical plane containing the tubes; by incremental rotation about the axis of the horizontal connecting tube; and by incremental rotation about a horizontal axis parallel to the thermosyphon tube axes. The results reveal similarities between the cranked and linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…In review [9], detailed analysis of the Rayleigh-Benard convection in a vertical cylinder with the height equal to its diameter is carried out, and it is shown that even in this simple and most studied geom etry, up to ten regions differing in the form of heat transfer in boundary layers and leading to different dependences of the Nusselt number (which is a mea sure of convective heat transfer intensity) on the Ray leigh and Prandtl numbers can be singled out on the plane of parameters "the Rayleigh number-Prandtl number." For long channels, a strong dependence of the heat transfer intensity on the angle of inclination is observed (e.g., Pr ~ 0.7 for long tubes filled with liquid helium [10] and Pr ~ 7 for thermosyphons with water [11]). The case of small Prandtl numbers (liquid met als for which Pr ~ 0.01 and smaller) remains studied less comprehensively even for short cylinders, and we are not aware of publications on free convection in long cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…In review [9], detailed analysis of the Rayleigh-Benard convection in a vertical cylinder with the height equal to its diameter is carried out, and it is shown that even in this simple and most studied geom etry, up to ten regions differing in the form of heat transfer in boundary layers and leading to different dependences of the Nusselt number (which is a mea sure of convective heat transfer intensity) on the Ray leigh and Prandtl numbers can be singled out on the plane of parameters "the Rayleigh number-Prandtl number." For long channels, a strong dependence of the heat transfer intensity on the angle of inclination is observed (e.g., Pr ~ 0.7 for long tubes filled with liquid helium [10] and Pr ~ 7 for thermosyphons with water [11]). The case of small Prandtl numbers (liquid met als for which Pr ~ 0.01 and smaller) remains studied less comprehensively even for short cylinders, and we are not aware of publications on free convection in long cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…This test has been motivated by some industrial applications. It has been proved that the heat transfer, in heat exchangers, is enhanced when the tube is optimally inclined [15]. The purpose of this test is to show the ability of IMM to predict the natural-convection flow in non-orthogonal grids.…”
Section: Buoyancy-driven Cavitymentioning
confidence: 98%
“…Это вызвано тем, что в наклонном положении резко улучшаются тепллогидравлические характеристики термосифона [1]. Экспериментальные исследования термосифона, заполненного водой, с диаметром трубы 20 мм показали, что при отклонении от вертикали на 60 º , коэффициент теплоотдачи для радиального потока тепла увеличивается в 3, 5-6 раз [9] . Исследования турбулентного режима теплообмена наклонного термосифона , заполненной жидким натрием, показали, что при отклонении от вертикального положения на 65º интенсивность теплообмена в осевом направлении увеличивается более чем в 10 раз [ 2].…”
Section: аннотацияunclassified